Evaluation of SARS-CoV-2 passive surveillance in Lithuanian mink farms, 2020–2021 - Žigaitė, Silvija; Masiulis, Marius; Bušauskas, Paulius; Pilevičienė, Simona; Buitkuvienė, Jūratė; Paulauskas, Vidmantas; Malakauskas, Alvydas (Frontiers in Veterinary Science, 2023)
The newly emerged SARS-CoV-2, causing COVID-19 in humans, is also infecting American mink (Neovison vison), used in fur production. Since 2020, passive surveillance of SARS-CoV-2 in mink farms was implemented in Lithuania. Here, we describe data from a survey of all 57 active Lithuanian mink farms carried out during November–December 2021 to complement passive surveillance in the country. In all 57 mink farms, nasopharyngeal swab samples were collected from dead or live mink and tested by real-time RT-PCR. Dead mink samples were tested in pools of 5, while live mink samples were tested individually. In 19 mink farms, blood serum was collected and tested for antibodies to determine previous exposure to the virus. Environmental samples from 55 farms were also collected and tested in pooled samples by real-time RT-PCR. The present survey has detected 22.81% viral RNA-positive mink farms and a high number of mink farms that were exposed (84.21, 95% CI 67.81–100%) to the virus. The increasing exposure of mink farms to the virus due to growing human COVID-19 cases and limitations of passive surveillance could explain the observed epidemiological situation of SARS-CoV-2 in Lithuanian mink farms, compared to the few positive farms previously detected by passive surveillance. The unexpected widespread exposure of mink farms to SARS-CoV-2 suggests that passive surveillance is ineffective for early detection of SARS-CoV-2 in mink. Further studies are needed to reveal the present status in previously infected mink farms.